Analysis of the Impact of Storytelling Methods on Early Childhood Religion and Moral Development - Ni Wayan Rasmini; I Wayan Karta (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
Activities of moral and religious development must also be promoted in preschool education. The purpose of this study was to analyses the impact of the storytelling method on the religious and moral development of early childhood. The study uses a quantitative method with an experimental post-test pre-test approach of a group design located at Cahaya Ananda Preschool, Mataram which is determined by a purposive cluster sampling. The subjects in this study were 52 children surveyed in classes B1, B2 and B3. The treatment was carried out four times using the storytelling method with tools, hand puppets, standing planel boards, paste and story books with environmental themes. There was an average increase; positive influence of the application of the learning method of storytelling on the religious/moral growth of early childhood. It is recommended that early childhood education teachers constantly improve their storytelling skills in order to be able to increase the potential of children, especially in the moral and religious development of early childhood